Study on the effect of GCY-12 gene on albendazole sensitivity of Haemonchus contortus by RNA interference - Chen, Xindi; Shi, Yaqin; Wang, Tengyu; Liu, Chunxia; Wang, Wenlong; Wang, Yu (Frontiers in Veterinary Science, 2025)
IntroductionHaemonchus contortus (H. contortus) is a common gastrointestinal nematode in small ruminants, posing a significant threat to the livestock industry. The control of H. contortus often depends on drugs such as albendazole. However, the prolonged and improper use of these drugs by livestock producers has led to widespread resistance among ruminant populations, posing a major challenge to parasite management. It is reported that the resistance of H. contortus to albendazole is related to the single nucleotide polymorphism (SNP) of β-tubulin homologous type I gene, but whether other genes are involved has not been reported.MethodsBased on the comparative analysis of the transcriptome sequencing data of albendazole-sensitive and albendazole-resistant strains of H. contortus, HCON_00043720 (Receptor-type guanylate cyclase GCY-12, GCY-12) gene was selected as the research object from the 23 differential genes in the cyclic guanosine monophosphate (cGMP) signaling pathway where the growth and development of H. contortus dauer stage is located. The GCY-12 gene of H. contortus eggs was silenced by RNA interference (RNAi) test. The reaction temperature was optimized, the expression of silenced eggs was detected by quantitative real-time polymerase chain reaction (qRT-PCR) technology, and the drug resistance of silenced eggs was detected by egg hatch assay (EHA).ResultsThe results showed that the gene expression level decreased significantly after GCY-12 interference, and the sensitivity of H. contortus to albendazole increased.DiscussionThis study highlights the potential role of GCY-12 in modulating albendazole resistance in H. contortus, offering new insights for developing effective therapeutic approaches.